Federal Court Cases: Integrated Data Base Bankruptcy Petitions, 2001 ([Verlag nicht ermittelbar], 2005)
The purpose of this data collection is to provide an official public record of the business of the federal bankruptcy courts. The data include all petitions filed under the Bankruptcy Code in the United States Bankruptcy Courts on or after October 1,1993, and any petitions filed before October 1, 1993, that were still pending on that date. The records in this file are organized according to the fiscal year of termination with cases still pending at the end of the year 2001 included in a separate pending dataset, not currently in this collection. For the bankruptcy data, the unit of analysis is a single case.